2014
DOI: 10.1002/dvdy.24170
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic expression of EphA receptor genes in mice supports their candidacy for involvement in cleft lip and palate

Abstract: Background Eph receptors, comprising the A- and B- subfamilies, are the largest family of receptor tyrosine kinases in the mammalian genome, and their function is critical for morphogenesis in a variety of contexts. Whereas signaling through B-type Ephs has been demonstrated to play a role in cleft lip and palate (CL/P), the involvement of A-type Ephs has not been examined in this context notwithstanding a recent genome-wide association study that identified the EPHA3 locus as a candidate for non-syndromic CL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…Interestingly, though complete loss of EPHB1, EPHB2, and EPHB3 resulted in a dramatic reduction in cell segregation in Efnb1 +/Δ ; Ephb1 -/-; Ephb2 -/-; Ephb3 -/embryos, segregation was not completely abolished, suggesting that additional receptors may play a role. Several EPHA receptors are strongly expressed in the secondary palate mesenchyme, including EPHA4, which was reported to interact with EPHRIN-B1 when overexpressed in Cos7 cells [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, though complete loss of EPHB1, EPHB2, and EPHB3 resulted in a dramatic reduction in cell segregation in Efnb1 +/Δ ; Ephb1 -/-; Ephb2 -/-; Ephb3 -/embryos, segregation was not completely abolished, suggesting that additional receptors may play a role. Several EPHA receptors are strongly expressed in the secondary palate mesenchyme, including EPHA4, which was reported to interact with EPHRIN-B1 when overexpressed in Cos7 cells [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…EPHA3 is expressed in the palatal shelves, face and middle ear of E14.5 mouse embryos (Visel et al, 2004 ). More recently, it has been suggested that mutations in EPHA family genes may cause cleft lip and palate (Agrawal et al, 2014 ). Mutations in the KIF7 gene have been reported to cause Acrocallosal syndrome, which presents with a wide range of craniofacial abnormalities including macrocephaly, hypertelorism, short nose, broad nasal bridge, short philtrum with upturned upper lip, high and narrow palate (Walsh et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the selected EphA receptors, we found that only EphA7 was co-expressed with EphA3 in the lung mesenchyme. Interestingly, a recent study has suggested that there is functional compensation of EphA3 loss by EphA7 co-expression during palate development, as compound homozygous mutation of EphA3 and EphA4 failed to cause defective midfacial development ( Agrawal et al, 2014 ). Furthermore, a truncated form of EPHA7 has been reported to act as a tumor suppressor in follicular lymphoma ( Oricchio et al, 2011 ), and it would thus be interesting to study its potential role in lung tumor suppression in conjunction with EphA3 loss of function.…”
Section: Discussionmentioning
confidence: 99%